Spatial modelling for rice production analysis in Central Java province Indonesia. (May 2019) - Karim, A; Sarra, D S; Wasono, R; Utami, T W; Toheri,
Abstract: Rice is one of staple food in Central Java province because rice is the main carbohydrate and calorie source for society in general. From year to year rice production in various regions in Indonesia shows a significant increase. Central Java is one of the provinces in Indonesia which has the agricultural sector as its main sector. However, in the last five years, the average rice production in Central Java showed a stagnant decline in value. This study was aimed to model the spatial effects on rice productivity in the cities in Central Java along with the factors that influence it. The method used is spatial modeling approach. The results of the analysis show that spatial lag X (SLX) model has the smallest AIC value, estimation result shows that rice production and harvest area have significant effect on rice productivity in Central Java.